Individual Microempreendedor: characterization of profile of entrepreneurs in Brazil - Moraes, Elenice da Silva (2018)
The present study aims to characterize the profile of the Individual Micro Entrepreneur (IME), formalized by the Mei Cadaster program in Brazil, in the period from July 2009 to June of 2017. The Individual Micro Entrepreneur is a program created through complementary Law n ° 128/2008 to motivate the formalization of autonomous workers who were not inserting into the formal lab our market. The data was collecting in government statistics institutes (IBGE, IPEA, and IRs). The study analyzes the entrepreneur MEI's profile according to the state to which it belongs, characterized by gender, age group, schooling and acting area. The analysis also presents the evolution of the quantity of MEI's from the creation of the program. It is concluding that the exploration of the evidenced profile can assist in the elaboration of strategies for the uptake of entrepreneurs for the institutional formalization of the Micros undertaking.